Studying the quality of drill pipes clamped in a wedge clamp - Afandiyev, Emin Musa; Nuriyev, Mahammadali Nuraddin (Eastern-European Journal of Enterprise Technologies, 2019)
Much attention has been recently paid to institutional measures aimed at improving quality of products related to petroleum machine building, in particular, the implementation of quality management systems based on the ISO standards of series 9000 [1]. However, technological methods of quality assurance have not been less important. The paper considers the factors influencing the quality of a cylindrical thin-walled component during operation. The most significant factors are the efforts to which the component us exposed when it is captured by a clamping mechanism. We have performed experiments into the effects of loads on a clamped component. The aim of these experiments was to establish the impact of various factors on stresses and deformations of cylindrical thin-walled components. The main factors, in addition to the applied forces, are the capturing angle of the clamping element, the length of its contact with a part, load distribution over the teeth of the clamping element. Given the development of deep drilling and an increase in loads acting on the wedge clamps, the requirements to their gripping capacity become stricter. Insufficient gripping capacity of the wedge clamp could cause damage to a pipe at the place it is clamped by wedges. In this case, clamping efforts act in the same region of a pipe, forming a thinned neck at long operation. The result of such damage is a premature failure of a drill pipe’s operation and the risk of an emergency. Significant impact on the gripping capacity of a wedge clamp is exerted by the elements of its design. Of importance is also the stressed state of a drill pipe clamped by a wedge clamp. We have calculated the optimal geometrical characteristics for clamping jaws. The best indicators were demonstrated by the grooved jaws with oblique intersecting notch. We have considered the load distribution over the teeth of clamping jaws. It has been shown that the optimal load distribution over the teeth is provided by jaws with oblique intersecting notch. In this case, tooth 1 accounts for 26 % of the load, tooth 2‒22 %, tooth 3‒19 %, tooth 4‒17 %, tooth 5‒16 %. The results obtained in the course of our research would make it possible to introduce such modifications to the design of clamping devices that could significantly improve their gripping capacity and reduce the risk of accidents